2022
DOI: 10.1111/odi.14255
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of preoperative Geriatric Nutritional Risk Index in oral squamous cell carcinoma

Abstract: Objectives To investigate the prognostic impact of preoperative Geriatric Nutritional Risk Index (GNRI) values in older adults undergoing radical surgery for oral squamous cell carcinoma (OSCC). Subjects and methods This retrospective study included 61 patients ≥65 years old with OSCC (43 men, 18 women; age: 72.1 ± 5.4 years) who underwent radical surgery between 2013 and 2020. Factors influencing overall survival (OS) and disease‐free survival (DFS) were examined. Results Receiver operating characteristic cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…It is calculated by the formula: GNRI = 1.487 × serum albumin (g/L) + 41.7 × present/optimal BW (kg) ( 11 ). In clinical settings, the GNRI is used as a simple nutrition evaluation approach, and a low GNRI indicates poor nutritional status of patients ( 12 , 13 ). In recent years, numerous studies have analyzed the role of GNRI in predicting the prognosis of DLBCL cases ( 14 20 ), but their findings remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…It is calculated by the formula: GNRI = 1.487 × serum albumin (g/L) + 41.7 × present/optimal BW (kg) ( 11 ). In clinical settings, the GNRI is used as a simple nutrition evaluation approach, and a low GNRI indicates poor nutritional status of patients ( 12 , 13 ). In recent years, numerous studies have analyzed the role of GNRI in predicting the prognosis of DLBCL cases ( 14 20 ), but their findings remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, seven were subsequently eliminated, mainly because they either did not report pertinent outcomes (only addressing perioperative complications without survival analysis) or were published as conference abstracts. Finally, ten retrospective studies [20][21][22][25][26][27][28][29][30][31] fulfilled the eligibility requirements and were incorporated into the final qualitative and quantitative analyses.…”
Section: Study Screening and Characteristics Of Studiesmentioning
confidence: 99%
“…Overall, the NOS scores varied from 5 to 8. Four of the studies were categorized as low quality, with scores ranging from 5 to 6, indicating a higher risk of bias [21,27,28,30]. The characteristics of the studies included in the analysis are summarized in Table 2.…”
Section: Study Screening and Characteristics Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutritional status in patients with cancer may be evaluated using the GNRI because it is a straightforward method. Previous research has revealed the predictive usefulness of the GNRI in many different forms of cancer, including gastric cancer (11), hepatocellular carcinoma (9), pancreatic cancer (12), and oral squamous cell carcinoma (13). The prognostic factor of GNRI in patients with UC has been the subject of several studies with varying results (14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%